2009
DOI: 10.1007/s10534-009-9230-7
|View full text |Cite
|
Sign up to set email alerts
|

Substrate role in the accumulation of heavy metals in sporocarps of wild fungi

Abstract: The distribution of neodymium, lead, thorium and uranium was investigated in about 100 samples of 12 different species of common, edible and non-edible mushrooms collected in unpolluted areas in the province of Ciudad Real, Central Spain. The quantitative analysis of heavy metals was performed by X-ray fluorescence spectrometry (a simple, accurate and non-destructive method). The concentration of these elements was related to three factors: mushroom specie, life style/substrate and study area. The results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 17 publications
3
43
2
5
Order By: Relevance
“…Particularly notable are the results of Borovička et al [23], who give concentrations for some heavy metals several orders of magnitude lower than those found in our analysis [24,25]. It must be noticed that, although the spectrometer was thoroughly calibrated, it seems that the methodology of X-ray fluorescence may not be adequate when the concentrations are close to the low detection limit (e.g., heavy metals).…”
Section: Resultscontrasting
confidence: 64%
“…Particularly notable are the results of Borovička et al [23], who give concentrations for some heavy metals several orders of magnitude lower than those found in our analysis [24,25]. It must be noticed that, although the spectrometer was thoroughly calibrated, it seems that the methodology of X-ray fluorescence may not be adequate when the concentrations are close to the low detection limit (e.g., heavy metals).…”
Section: Resultscontrasting
confidence: 64%
“…3) in the mine dump waste recorded in this study. Related studies on mycoremediation have indicated that contaminant heavy metals can be biosorbed by mushroom bodies at binding sites found in the cellular structure [20]. In the current study, it is suggested that among the various reactive compounds associated with fungal cell walls, the extracellular polymeric substances reported by Gutierrez et al [21] were of particular importance and are known to have significant effects on acid-base properties and metal adsorption [22][23][24].…”
Section: Concentrations Of Heavy Metals and Ph In Mine Dumps After Grmentioning
confidence: 62%
“…In this respect, the oyster mushroom's capacity as a biosorbent of Mn 2+ , Fe 3+ and Cd 2+ from pyritic mine waste dumps was re-confirmed by the fact that their concentrations after bioremediation (treatment 5) at the four study sites were lower than the LSL by 1.92 mg kg −1 (20%), 1.43 mg kg −1 (39%) and 1.65 mg kg −1 (55%), respectively. Mushroom substrate is a kind of lignocellulose material which supports the growth, development and fruiting of mushroom [2,4,20]. Previous studies by Demirbas [19], Gavrilescu [6], Kojta and Zhang [26] have reported that an ideal substrate will contain enough nitrogen and carbohydrate for rapid mushroom growth.…”
Section: Concentrations Of Heavy Metals and Ph In Mine Dumps After Grmentioning
confidence: 99%
“…However, both fungi and other fractions, for example, the rhizosphere and soil-root interface fractions, were noticeably enriched with Cd, although this was only significant for the soil-root interface fraction. The capability of fungal species for accumulating essential (Co, Ni) and nonessential (Pb) metals differs [16,17]. The Co, Ni, and Pb concentrations were generally evenly distributed between soil fractions and mycelium, whereas the concentration of these metals in sporocarps was lower.…”
Section: Discussionmentioning
confidence: 99%
“…However, the capacity for retaining metal among species of fungi is wide [16] and the capability of fungi to accumulate elements differs [17]. Essential nutrients, such as cobalt (Co) and nickel (Ni), and nonessential lead (Pb) appear to be excluded from fungi, as they do not accumulate [18,19].…”
Section: Introductionmentioning
confidence: 99%